The politics of persuasion. Opinion-shaping activities and gender equality in Sweden, 1960-1970. (3rd July 2019) - Lundqvist, Åsa
ABSTRACT: In this paper, the role and significance of opinion-shaping and persuasion activities are explored through an analysis of the activation of women in the Swedish labour market in the 1960s, highlighting the ways in which gender equality ideals became infused in these activities through a process of 'transformative state feminism'. The analysis draws on qualitative data including archival material and interviews. Activation policies in the 1960s emphasised the ideology of full employment including the importance of increasing women's participation in paid work, hence paving the way for a dual-earner family model. The concrete measures associated with implementation of such policies were carried out by the National Labour Market Board (AMS), and included retraining and advanced training courses but also a number of innovative opinion-shaping activities. Two of these are analysed in this paper: a radio series called 'Housewife switches job' and the establishment of a so-called 'activation inspector'. Following this analysis, the underlying ideas permeating such opinion-shaping activities and the actors who infused ideals of gender equality into the process are examined. In conclusion, lessons for the ongoing transformation of traditional gender relations and prospects for future advances in gender equality are discussed.